WHICH OF THE TWO LANGUAGES POTENTIALLY LEADS TO DEATH EARLIER?: KUALUH MALAY OR JAVANESE ? - Nidaul . Husna; Amrin . Saragih; Anni Holila Pulungan (LINGUISTIK TERAPAN, 2023)
Local languages are often used less frequently, especially in various formal (official) fields such as government and education. Moreover, the multi-ethnic nature of Indonesian society, with its own language and culture, certainly opens up opportunities for contact through inter-ethnic communication and interaction with different languages and cultures. Some phenomena are interesting to study because these phenomena can become conditions that lead to the extinction of a language. This has become the concern of various groups, especially linguists who are very interested in this field. This is of course very reasonable because the phenomenon of the extinction of a language does not only have implications for the linguistic dimension itself which pays attention to aspects of language and the structures in it. This study aims to find out how the attitude of local language users in using their regional languages and there are two regional languages studied in the North Labuhanbatu area and what language predictions are endangered. Based on the results of the discovery, the endangered language in the North Labuhanbatu area is Javanese compared to the Malay language.